Uma geografia da fórmula 1: geopolítica, circuitos e espacialidades - Ana Beatriz Castro de Jesus; Ricardo José Batista Nogueira (Confins)
The aim of this text is to briefly reflect on the relationship between geopolitics and motor racing. Based on a bibliographical survey predominantly in English literature, it was observed that the dynamics of choosing host countries, as well as the partnerships between teams, permeate issues that transcend sporting interests and involve questions of political and economic interests. In addition, the influence of conflicts and wars on motorsport stands out.